2006
DOI: 10.1590/s0101-20612006000400014
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade protéica da carne de novilho precoce alimentado com lipídios protegidos

Abstract: 0,05) entre as dietas experimentais e a dieta padrão (caseína) para PER, NPR e digestibilidade, sendo que os valores médios variaram entre 3,89 e 4,74 (98,06 e 119,34%, em relação à caseína); 4,80 e 5,65 (101,07 e 118,94%, em relação à caseína) e de 92,49 a 95,48 (97,24 a 100,39%, em relação à caseína), respectivamente. Verificou-se que a carne de todos os grupos experimentais apresentou alta qualidade protéica, equiparando-se à da caseína, exceto o grupo genético Aberdeen Angus X Nelore, alimentado com a diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
1
4
0
2
Order By: Relevance
“…The results show that the animals receiving the G1 diet (protein-free) showed anegative meanweight gainof -10.7g, indicating that, as expected, weight loss occurred during the experiment [20].…”
Section: Evaluation Of Protein Qualitysupporting
confidence: 68%
“…The results show that the animals receiving the G1 diet (protein-free) showed anegative meanweight gainof -10.7g, indicating that, as expected, weight loss occurred during the experiment [20].…”
Section: Evaluation Of Protein Qualitysupporting
confidence: 68%
“…Soy and quinoa rates, either as flakes or flour, caused the high levels of carbohydrates since quinoa is rich in fibers and carbohydrates. Several studies showed that these foods are not merely a source of carbohydrates but also of phytochemicals which are highly important for the organism (BEHRENS; DA SILVA, 2010;NAVES, 2014;PIRES, 2006). The hamburger also revealed high fiber rates due to the material used.…”
Section: Resultsmentioning
confidence: 99%
“…They also contribute towards homeostasis by keeping an osmotic balance between the organism´s several fluids. Due to their structure, proteins are capable of combining themselves with acid or base compounds and thus keep the acid-base equilibrium between blood and the organism´s different tissues (SBUZZI, 2013;PIRES, 2006;MOREIRA, et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations